GAGASAN KEWAJIBAN MAHKAMAH KONSTITUSI DALAM MEMBERIKAN FATWA PENCABUTAN KEWARGANEGARAAN UNTUK WARGA NEGARA INDONESIA MANTAN ANGGOTA ISIS - Saifulloh, Putra Perdana Ahmad (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2023)
AbstractAccording to Article 23 Paragraph (1), Letter d of the Citizenship Law, Indonesian citizens lose their citizenship status for several reasons, namely it is wrong to become a foreign soldier without prior permission from the President. This is reinforced by the regulation in PP No. 2 of 2007, the revocation was carried out by the president must go through a legal process. The legal process referred to is not the litigation process, but the HAN process, namely the Menkumham examines, after being reviewed it is feasible to revoke the status of the former ISIS member's Indonesian citizen, then the Menkumham submits it to the President, and continues with the issuance of a Presidential Decree. However, there is a problem, if the Government complies with the positive law regarding the revocation of the status of Indonesian citizens. Ex-members of ISIS seem undemocratic, because it is only based on a Presidential Decree issued based on the recommendations of the Ministry of Law and Human Rights. For this reason, the author is interested in writing about the revocation of the status of Indonesian citizens who are former members of ISIS which is in accordance with the concept of a democratic rule of law, but also prioritizes effectiveness and time efficiency. The author considers that the revocation of the status of Indonesian citizens who are ex-ISIS members by the government is something that is logical for now, but the government before revoking the status of Indonesian citizens who are ex-ISIS members must ask for consideration from the Constitutional Court as a bodyguard, and interpreters of Pancasila and the Constitution through the revision of the Constitutional Court Law and the Citizenship Law. AbstrakMenurut Pasal 23 Ayat (1), Huruf d UU Kewarganegaraan, WNI kehilangan status kewarganegaraannya dengan beberapa alasan, yaitu salah menjadi tentara asing tanpa izin terlebih dahulu dari Presiden. Hal ini diperkuat oleh pengaturan dalam PP No.2 Tahun 2007, pencabutan itu dilakukan oleh presiden harus melalui proses hukum. Proses Hukum yang dimaksud bukan Proses Litigasi, akan tetapi Proses HAN, yakni Menkumham memeriksa, setelah dikaji layak untuk dicabut status WNI Mantan Anggota ISIS ini, selanjutnya Menkumham menyerahkan ke Presiden, dan dilanjutkan dengan dikeluarkan Keppres. Akan tetapi ada problematik, jika Pemerintah tunduk pada hukum positif tentang pencabutan status WNI Mantan Anggota ISIS terkesan tidak demokratis, karena hanya berdasarkan Kepres yang dikeluarkan berdasarkan Rekomendasi Kemenekumham. Untuk itulah Penulis tertarik untuk menulis tentang pencabutan status WNI Mantan Anggota ISIS yang sesuai dengan konsep Negara hukum yang demokratis, tetapi juga mengedepankan efektivitas, dan efisiensi waktu. Penulis menilai pencabutan status WNI Mantan Anggota ISIS oleh Pemerintah adalah sesuatu yang logis untuk saat ini, akan tetapi Pemerintah sebelum mencabut status WNI Mantan Anggota ISIS harus meminta pertimbangan dari MK sebagai pengawal, dan penafsir Pancasila dan Konstitusi melalui Revisi UU MK dan UU Kewarganegaraan.